Wage Effects of Educational Mismatch According to Workers' Origin: The Role of Demographics and Firm Characteristics - Valentine Jacobs; Francois Rycx; Mélanie Volral (Institute of Labor Economics (IZA), 2021)
This paper examines the influence of educational mismatch on wages according to workers' region of birth, taking advantage of our access to rich matched employer-employee data for the Belgian private sector for the period 1999-2010. Using a fine-grained approach to measuring educational mismatch and controlling for a large set of covariates, we first find that workers born in developed countries benefit from positive wage returns to their years of attained-, required and over-education, and that these returns are significantly higher for them than for their peers born in developing countries. Second, our results show that the wage return to a year of over-education is positive but lower than that to a year of required education. This suggests that over-educated workers suffer a wage penalty compared to their well-matched former classmates (i.e. workers with the same level of education in jobs that match their education). However, the magnitude of this wage penalty is found to vary considerably depending on the origin of the workers. Indeed, all else being equal, our estimates show that it is much greater for workers from developing countries – especially for those born in Africa and the Middle and Near East – than for those from developed countries. Regardless of workers' origin, our estimates further indicate that the wage penalty associated with over-education is higher for workers who: i) have attained tertiary education, ii) are male, iii) have more seniority in employment, iv) are employed in smaller firms, and v) are covered by a collective agreement at the firm level. Yet, whatever the moderating variable under consideration, the estimates also show that the wage penalty associated with over-education remains higher for workers born in developing countries.
Keywords: I24; I26; J15; J24; J31; 330; immigrants; educational mismatch; wage gap; linked employer-employee data